The Nature and Patterns of Nigeria–India Economic Relations: A Historical Analysis. Issue 2 (July 2017) - Eiguedo-Okoeguale, H. E.
External relations between states are not conducted in a vacuum; they are conducted within particular contexts. Over the years, a number of factors have determined the relations and patterns of interactions between Nigeria and India. This study focuses on the economic aspects of Indo-Nigerian relations and explores how they have affected nation-building efforts in the two countries. It argues that as postcolonial states, the economic relations between Nigeria and India are continuously guided by the principles of identity, reciprocity and interdependence. It further argues that, although India and Nigeria have different levels of development, economic relations between the two countries are conducted using the non-zero-sum game approach, which makes it possible for both the countries to mutually gain (or lose) depending on the commodities of trade or investment area. This article is organised in five sections. The first is the introduction, which lays the background for the study. The second aspect focuses on the nature of India's economy since independence. The third part examines Nigeria's economic sector, while the fourth section discuses Indo-Nigerian investment relations. The fifth section concludes the article and provides recommendations for policymakers. It establishes that trade and joint investments yield development and prosperity to both countries by providing opportunities for national integration.